2022
DOI: 10.3390/biom12020205
|View full text |Cite
|
Sign up to set email alerts
|

Plant SWEET Family of Sugar Transporters: Structure, Evolution and Biological Functions

Abstract: The SWEET (sugars will eventually be exported transporter) family was identified as a new class of sugar transporters that function as bidirectional uniporters/facilitators and facilitate the diffusion of sugars across cell membranes along a concentration gradient. SWEETs are found widely in plants and play central roles in many biochemical processes, including the phloem loading of sugar for long-distance transport, pollen nutrition, nectar secretion, seed filling, fruit development, plant–pathogen interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 128 publications
1
44
0
5
Order By: Relevance
“…The SWEET family plays a vital role in the long-distance transport of sugars, such as glucose, fructose, and sucrose, and NIP5;1 is also involved in sugar transport . In VIGS assays (Figures F and F), the fructose and sucrose contents were higher in leaves, while they were lower in fruits from SWEET4 -silenced plants, which proved that SWEET4 was mainly responsible for the long-distance transport of fructose and sucrose from leaves to fruits.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The SWEET family plays a vital role in the long-distance transport of sugars, such as glucose, fructose, and sucrose, and NIP5;1 is also involved in sugar transport . In VIGS assays (Figures F and F), the fructose and sucrose contents were higher in leaves, while they were lower in fruits from SWEET4 -silenced plants, which proved that SWEET4 was mainly responsible for the long-distance transport of fructose and sucrose from leaves to fruits.…”
Section: Discussionmentioning
confidence: 76%
“…Our data revealed that the expression levels of NIP5;1 and SWEET4 were significantly affected by B under CGMMV infection. Additionally, NIP5;1 is a major B channel protein to uptake B, and NIP5;1 and SWEET were all involved in sugar transport. , In consideration of the above reasons, we selected NIP5;1 and SWEET4 for VIGS assays to uncover their roles in viral resistance and the functions for regulating the homeostasis of nutrient elements, soluble sugars, and cell wall polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of carbohydrates and nitrogen which need transporter proteins to move to drought-resistant roots, on the one hand, is from detached leaves, and on the other hand, is from photosynthesis ( Yildirim et al., 2018 ; Han et al., 2019 ). The bidirectional sugar transporter (SWEET14) and nitrate transporter 1/peptide transporter (NRT1/PTR), were two significantly accumulating proteins in drought-resistant grapevine rootstock 110R, which promoted the carbohydrates and nitrogen accumulation in roots ( Chen et al., 2012 ; Yildirim et al., 2018 ; Ji et al., 2022 ). Although we believe that during drought stress, transporter proteins will accumulate in the grafted plants, the underlying regulated pathways need further investigation.…”
Section: Rootstock Changesmentioning
confidence: 99%
“…Further, it can regulate the uptake of glucose through the cell membrane in the form of glucose transporters, with the function of bidirectional sugar transporters [ 16 ]. A typical SWEET protein consists of seven transmembrane domains (TMs), of which three are more conserved TMs that form the MtN3/saliva structural domain, and the middle is connected by a less conserved TM [ 17 ]. Studies have shown that SWEET proteins can homo- and heterooligomerize to create functional pores; thus, providing transport channels and driving their functions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%